Clinical Characteristics of Patients with Aggressive Systemic Mastocytosis and Efficacy Analysis of Systemic Therapies: A Monocentric Real-World Experience - açar, ibrahim halil; Guvenc, Birol (International Journal of Innovative Research in Medical Science, 2023)
Introduction and Objective: Aggressive systemic mastocytosis is a lethal disease with poor prognosis in which organ damage due to mast cell activation is observed and response to medical treatment is low. The aim of this study was to evaluate the clinicopathological characteristics of ASM patients and the efficacy of cytoreductive treatments. Patients and methods: The clinicopathological features and survival analyses of 27 patients who were followed up with a diagnosis of aggressive systemic mastocytosis (ASM) and treated with cytoreductive therapy between 2017 and 2021 in our center were evaluated. Results: The mean age of the patients was 59 years and there was a slight male gender predominance (5: 4). KITD816V mutation was positive in 85% of cases. The most common symptoms at the time of diagnosis were fatigue, pruritus and dyspeptic complaints, respectively. The number of patients evaluable for response to imatinib, peginterferon alfa-2a (Peg-Ifn), cladribine and midostaurin treatments were 4, 7, 8 and 8, and the overall (partial) response rates were 25% (25%), 42% (28%), 50% (38%) and 37% (25%), respectively. Most of the responses were partial (PR) and major response (MR) was seen in very few patients. Increasing ECOG score, serum tryptase level, spleen size, and WBC count increased mortality, while decreasing hemoglobin level increased mortality. General median overall survival (OS) was 27.74 months (35.11-143.88). Two-year survival rate was 88.9% and 5-year survival rate was 63.1%. Median overall disease-free survival (DFS) was 10.86 months (9.27-12.50). Two-year DFS was 22.2%, while 5-year DFS was only 7.4%. Conclusion: The depth of response and response rates of the current therapies used in the treatment of ASM are quite low and insufficient to control the disease. Since there is an unmet therapeutic area in the treatment of ASM, there is a need for the development of new treatment modalities.